Pengaruh Kadar Air terhadap Karakteristik Tegangan Tembus dan Dielektrik Isolasi Kertas-Minyak - Andhang Windarto; Suharyanto; T. Haryono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Paper impregnated oil (paper-oil insulation) is used as insulation material in transformer. The water in transformer appears as a consequence of oxidation process of the paper-oil system and atmospheric air penetration into the tank. High voltage testing is used to test paper-oil insulation with different water content to examine its breakdown voltage. Three conditions were used in this research, which are initial condition, the condition after heating up to 700C, and the condition after cooling down at room temperature for 2 x 24 hour. The result of high voltage tests shows that the water content can decrease the breakdown voltage and the dielectric strength of paper-oil insulation. The heating-cooling process reduces the water content of oil insulation and therefore increases the breakdown voltage and dielectric strength of paper-oil insulation.